Gust load alleviation of an unmanned aerial vehicle wing using variable camber. (May 2014) - Bernhammer, Lars O; Teeuwen, Sjors PW; De Breuker, Roeland; van der Veen, Gijs J; van Solingen, Edwin
It is vital for an unmanned aerial vehicle to meet contradictory mission requirements originating from different tasks this type of aircraft has to fulfill. The ability to switch between configurations greatly expands the range of possible missions. An unmanned aerial vehicle wing has been developed to demonstrate the capacity to optimize the aerodynamic and structural performances according to the mission stage. The wing is equipped with four macro fiber composite benders that can be controlled individually, and each of these macro fiber composite benders actuates a section of the wing. A numerical study was conducted with XFLR5 to determine the optimal configurations of the flap positions for both range and endurance. A wind tunnel study was performed to verify these results. During the experiment, a maximum attainable increase in lift coefficient of 0.072 could be achieved, while numerically the increase was computed to be 0.079. The wide-frequency bandwidth of the actuators allows using the developed system also for other purposes such as load alleviation. Unmanned aerial vehicles are often light and fly at low airspeeds, which make them very sensitive to gust excitation. For this purpose, the experimental model was equipped with two accelerometers to measure the amplitude of the first two deformation modes. Significant load alleviation capacities with reductions up to 50% in load amplitude could be achieved. This reduction was achieved, even though the wing box contributes largely to the structural damping, as the foam for the construction absorbs a significant proportion of the vibrations.